2021
DOI: 10.1080/23744235.2021.1945139
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS-CoV-2 variant B.1.1.7 among vaccinated health care workers

Abstract: Background Vaccination against COVID-19 is among the most effective measures to stop the spread of the disease. However, acceptance of vaccination against COVID-19 among HCWs has not been universal and emergence of new variants with increased transmissibility, reduced neutralization by BNT162b2 vaccine-elicited sera and ability to cause breakthrough infections in vaccinated individuals is concerning. The aim of this study was to compare viral load, clinical presentation at diagnosis and type of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 14 publications
2
33
0
Order By: Relevance
“…Indeed, a 2021 study [18] evaluated the efficacy of the vaccine on antibody production and its side effects in health personnel with and without prior SARS-CoV-2 infection and in a group of unvaccinated individuals with prior COVID-19; the authors reported the production of 100% neutralizing antibodies in both groups after the second dose and well-tolerated adverse effects. On the other hand, Ioannu P et al [19] reported a potentially reduced efficacy of BNT162b2 in preventing the transmission of variant B.1.1.7. These results may encourage vaccination among still-reluctant HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a 2021 study [18] evaluated the efficacy of the vaccine on antibody production and its side effects in health personnel with and without prior SARS-CoV-2 infection and in a group of unvaccinated individuals with prior COVID-19; the authors reported the production of 100% neutralizing antibodies in both groups after the second dose and well-tolerated adverse effects. On the other hand, Ioannu P et al [19] reported a potentially reduced efficacy of BNT162b2 in preventing the transmission of variant B.1.1.7. These results may encourage vaccination among still-reluctant HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Ct value was negatively correlated with the number of infected CPs per IP. Most previous studies have described comparable Ct values in vaccinated and unvaccinated IPs [8,22,23]. However, it must be noted that our study analyzed Ct levels only once, during PCR testing.…”
Section: Discussionmentioning
confidence: 86%
“…Studies of viral load in vaccinated but infected individuals have illustrated that less virus is shed in the nasopharynx by vaccinated individuals (Levine- Tiefenbrun et al, 2021;McEllistrem et al, 2021;Pritchard et al, 2021), but there are currently no data on shedding of SARS-CoV-2 viral fragments in stool from infected but vaccinated individuals. Moreover, a study of healthcare workers where the alpha variant was dominant reported no difference in viral load by vaccination status (Ioannou et al 2021), and preliminary analysis from England has not identified noticeable differences in WW through to March 2021 (Hoffman et al 2021b).…”
Section: Discussionmentioning
confidence: 99%